“ANALYSIS AND RETRAINING OF THE BERT MODEL FOR THE UZBEK LANGUAGE: METHODS AND RESULTS” (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This paper discusses the use of the BERT model for processing texts in the Uzbek language. BERT (Bidirectional Encoder Representations from Transformers), being one of the most advanced models in the field of natural language processing (NLP), demonstrates high efficiency when working with various languages. The study analyzes the main aspects of adapting BERT for the Uzbek language, including data collection and preparation, model training and evaluation of its performance.